STRUKTUR SEMANTIK VERBA “MEMBAWA” BAHASA OSING BANYUWANGI - I Gde Yudhi Argangga Khrisnantara; I Nengah Sudipa (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
The aim of this research is to determine the real meaning of lexical verbs “membawa” in osing language (Banyuwangi). The data is collecting by interviews and observation of informan from Banyuwangi, East Java. The method used in this research is descriptive-qualitative. The theory used in this analysis is the theory of Natural Semantic Metalanguage (NSM). The verb membawa “bring” explains something to be brought of head to hand. The verb membawa with polysemy composition act, namely do and move to the other entity part and located at a place on certain part of human body. Using paraphrase technique, furthermore it turns out that the lexicon “membawa” who has similar or different paraphrase depending on semantic prime. The result of the analysis showed that the verb ‘membawa’ in osing language can be described in several lexicons: nyangking, mikul, nyuwun, ngѐndong, and ngemplok.